Information Communication Technology in EFL Classroom - Khalid Beni Akhy; Weningtyas Parama Iswari (Journal of English as A Foreign Language Teaching and Research, 2021)
Information Communication Technology (ICT) has penetrated into the teaching of English as a foreign language (EFL) around the world, not to mention in Morocco. However, due to some obstacles faced in its implementation, its effectiveness needs to be improved. This paper is intended to explore the potentials of ICT to be used in EFL classes in Morocco and how to prepare teachers to be ready in incorporating the ICT in their language teaching.  The potentials cover, among others, what multimedia resources are available, how to make use of them and how ICT becomes the tools to develop student's English language skills. As the teachers' role is very significant, they should get professional development training in ICT for education